Shape memory polymer with high tensile capacity and preparation method thereof

By preparing a high-stretching shape memory polymer with an annular topology, the adaptation problems of flexible electronics and aerospace equipment on complex stress environments and irregular surfaces are solved, and the high-efficiency mechanical properties and shape memory properties of the material are achieved.

CN119798591AActive Publication Date: 2025-04-11HARBIN INST OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411882099.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-11
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Flexible electronics and aerospace equipment needs to withstand complex stress environments and adapt to irregular surfaces, and existing materials are difficult to meet these needs.

Method used

A high-stretching capacity shape memory polymer is used, and the preparation method includes dissolving butyrolactone and ethylene glycol in toluene, adding alkynyl compounds and other compounds after heating, and after a series of reactions and crosslinking steps, finally obtaining a shape memory polymer with a cyclic topological structure.

Benefits of technology

The prepared shape memory polymer has good mechanical properties, tensile properties and shape memory properties, and can adapt to irregular surfaces in complex stress environments. It is suitable for biomedical, medical equipment, wearable devices, robotics and aerospace fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198444720000021
    Figure BDA0005198444720000021
  • Figure BDA0005198444720000032
    Figure BDA0005198444720000032
  • Figure BDA0005198444720000033
    Figure BDA0005198444720000033
Patent Text Reader

Abstract

The invention discloses a high-tensile-capacity shape memory polymer and a preparation method thereof, and belongs to the technical field of shape memory polymer synthesis. The method comprises the following steps: dissolving butyrolactone and ethylene glycol in toluene, heating and stirring; cooling to room temperature, adding a compound 1, stirring at room temperature for 20-24 hours, and collecting an organic layer to obtain white powder; dissolving the white powder and a compound 2 in methylbenzene, heating to 60-75 DEG C, maintaining a reaction mixture for 48 hours, then cooling to room temperature, and adding excessive diethyl ether to obtain a compound 3; the preparation method comprises the following steps: sequentially adding siloxane, a compound 3 and hexamethylene diisocyanate into tetrahydrofuran, stirring to obtain a prepolymer, adding a cross-linking agent methacrylic acid, and stirring; and drying the solution at 90-110 DEG C for 10-14 hours. According to the invention, a cyclic topological structure is introduced into a siloxane material, so that the shape memory polymer is endowed with relatively strong tensile property, and the prepared shape memory polymer has very good mechanical property, tensile property and shape memory property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of shape memory polymer synthesis, and in particular relates to a high-stretchability shape memory polymer and a preparation method thereof. Background Art

[0002] Shape memory polymers are a class of smart materials that can respond to external stimuli and return to their original shape from a pre-designed temporary shape. These materials have the advantages of light weight, large deformation, easy programming, and adjustable elastic modulus, and have shown high application value in many application fields in the past three decades.

[0003] In modern society, with the rapid development of flexible electronic technology, especially in the fields of artificial electronic skin, wearable devices, soft robots, etc., the demand for stretchable flexible materials is growing. High-stretchability shape memory polymers have become key materials in this field due to their unique properties. The material properties of polymers with cross-linked network structures are closely related to the chemical composition of the repeating units. Among them, the topological structure plays an important role in the polymer network. Ring polymers as topoisomers of their linear precursors have different properties, such as smaller hydrodynamic volume, higher glass transition temperature, and higher density. The use of cyclic crystalline polymers as part of the cross-linked polymer network structure improves the stretchability of the cross-linked polymer. It can solve the problem that when the aircraft takes off, lands, and changes in different flight postures, the wings are subjected to different airflow pressures and temperature changes, and the shape needs to be changed to optimize the aerodynamic performance. It can also be used in flexible electronics to solve the problems of irregular human body surface and complex stress environment. Summary of the invention

[0004] The purpose of the present invention is to solve the problems that flexible electronic and aerospace equipment need to withstand complex stress environments and adapt to irregular surfaces, and to provide a high-stretchability shape memory polymer and a preparation method thereof.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a high-stretchability shape memory polymer, the method comprising:

[0007] Step 1: Dissolve butyrolactone and ethylene glycol in toluene, heat to 100-115°C and stir for 2-3h;

[0008] Step 2: After cooling to room temperature, add compound 1 having alkynyl groups at both ends, and stir at room temperature for 20-24 hours, collect the organic layer, dry it, and evaporate it under reduced pressure to obtain a white powder;

[0009] Step 3: dissolving the white powder and compound 2 in toluene, heating the reaction mixture to 60-75°C and maintaining the temperature for 48 hours, then cooling to room temperature, adding an excess of ether relative to the remaining liquid, filtering and drying to obtain compound 3;

[0010] Step 4: Add siloxane, compound 3, and hexamethylene diisocyanate to tetrahydrofuran in sequence, stir for 1-1.5 hours at 60-75° C. to obtain a prepolymer, add methacrylic acid as a crosslinker in an amount of 1 / 3 of the total mass of siloxane, compound 3, and hexamethylene diisocyanate, and stir for 1-1.5 hours;

[0011] Step 5: Pour the solution into a mold and place it in an oven at 90-110°C for 10-14 hours to obtain a shape memory polymer.

[0012] Furthermore, in step 1, the mass fractions of glycine butyrolactone and ethylene glycol are 97wt.% to 98.6wt.% and 1.4wt.% to 3wt.% respectively; preferably, the mass fractions of glycine butyrolactone and ethylene glycol are 98.6wt.% and 1.4wt.% respectively.

[0013] Furthermore, in step 2, the synthesis method of compound 1 is:

[0014] Succinic anhydride and 4-methylaminopyridine in a mass ratio of 3-4:1 are dissolved in dichloromethane, and then propargyl alcohol is added dropwise to the above suspension, the mass ratio of 4-methylaminopyridine to propargyl alcohol is 2.5-3:1, and stirred at room temperature for 22-24 hours. After the reaction is completed, wash with 10% NaHSO4 and then with deionized water, collect the organic phase, and then dissolve N, N'-dicyclohexylcarbodiimide in dichloromethane, and add dropwise to the above organic phase, the mass ratio of 4-methylaminopyridine to N, N'-dicyclohexylcarbodiimide is 2.5-3:1. After reacting at 0°C for 1 hour, let stand to room temperature and stir for 20-24 hours. Filter the reaction mixture to remove all solids, and evaporate under reduced pressure to obtain compound 1.

[0015] Furthermore, in step 2, the mass ratio of compound 1 to butyrolactone is 1:6.

[0016] Furthermore, in step three, the synthesis method of compound 2 is: adding a mixture of 1,4-butanediol diglycidyl ether, NaN3 and NH4Cl in a mass ratio of 15-18:24:20 to dichloromethane, stirring at 40-60°C for 20-24h, cooling to room temperature, washing with 10% NaHSO4, then washing with deionized water, and evaporating under reduced pressure to obtain compound 2.

[0017] Furthermore, in step three, the mass ratio of compound 2 to white powder is 1:10.

[0018] The synthesis of compound 3 involves the reaction shown in formula (III):

[0019]

[0020]

[0021] Furthermore, in step 4, the structural formula of the siloxane is:

[0022]

[0023] In formula (I), R1 is NH2, R2, R3, R4, R5, R6, and R7 are independently selected from H, C 1-10 Alkyl, C 6-14 One or more of aromatic groups.

[0024] Furthermore, in step 4, the mass ratio of the siloxane, compound 3, and hexamethylene diisocyanate is 8:10 to 13:1.

[0025] The reaction process of shape memory polymer involves the equation shown in formula (II):

[0026]

[0027] A high-stretchability shape memory polymer prepared by the above preparation method.

[0028] The beneficial effects of the present invention compared to the prior art are as follows: the present invention selects a siloxane material with good tensile properties, introduces a ring topological structure therein, and gives the shape memory polymer a strong tensile property. The prepared shape memory polymer has excellent mechanical properties, tensile properties and shape memory properties, and is expected to be applied in biomedicine, medical equipment, wearable devices, robotics, aerospace and other fields. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0030] Example 1

[0031] A method for preparing a high-stretchability shape memory polymer comprises the following steps:

[0032] (1) Dissolve 24.6 g of butyrolactone and 0.35 g of ethylene glycol in 20 mL of toluene, heat to 100 °C and stir for 2 h;

[0033] (2) After cooling to room temperature, 4.1 g of compound 1 was added, and the mixture was stirred at room temperature for 24 h. The organic layer was collected, dried, and evaporated under reduced pressure to obtain a white powder. The synthesis method of the compound 1 is as follows: succinic anhydride and 4-methylaminopyridine in a mass ratio of 3:1 were dissolved in dichloromethane, and then propargyl alcohol was added dropwise to the above suspension, wherein the mass ratio of 4-methylaminopyridine to propargyl alcohol was 2.5:1, and the mixture was stirred at room temperature for 22-24 h. After the reaction was completed, the mixture was washed with 10% NaHSO4 and then with deionized water. The organic phase was collected, and then N, N'-dicyclohexylcarbodiimide was dissolved in dichloromethane and added dropwise to the above organic phase, wherein the mass ratio of 4-methylaminopyridine to N, N'-dicyclohexylcarbodiimide was 2.5:1. After reacting at 0°C for 1 h, the mixture was allowed to stand to room temperature and stirred for 20-24 h. The reaction mixture was filtered to remove all solids, and evaporated under reduced pressure to obtain compound 1.

[0034] (3) 20 g of white powder and 2 g of compound 2 were dissolved in 20 mL of toluene, the reaction mixture was heated to 70°C and maintained for 48 h, and then cooled to room temperature. 30 mL of ether was added, and compound 3 was obtained after filtering and drying; the synthesis method of compound 2 was as follows: a mixture of 1,4-butanediol diglycidyl ether, NaN3 and NH4Cl in a mass ratio of 15:24:20 was added to dichloromethane, stirred at 50°C for 20-24 h, cooled to room temperature, washed with 10% NaHSO4, then washed with deionized water, and evaporated under reduced pressure to obtain compound 2.

[0035] (4) 8 g of siloxane, 10 g of compound 3, and 1 g of hexamethylene diisocyanate were added to 10 mL of tetrahydrofuran in sequence, and stirred at 60° C. for 1 h to obtain a prepolymer, and 6.6 g of methacrylic acid, a crosslinking agent, was added and stirred for 1 h; the structural formula of the siloxane is:

[0036]

[0037] In formula (I), R1 is NH2, and R2, R3, R4, R5, R6, and R7 are CH3.

[0038] (5) The solution was poured into a mold and placed in an oven at 100° C. for 12 h to obtain a shape memory polymer.

[0039] Example 2

[0040] A method for preparing a high-stretchability shape memory polymer comprises the following steps:

[0041] (1) Dissolve 24.6 g of butyrolactone and 0.35 g of ethylene glycol in 20 mL of toluene, heat to 100 °C and stir for 2 h;

[0042] (2) After cooling to room temperature, 4.1 g of compound 1 was added, and the mixture was stirred at room temperature for 24 h. The organic layer was collected, dried, and evaporated under reduced pressure to obtain a white powder. The synthesis method of the compound 1 is as follows: succinic anhydride and 4-methylaminopyridine in a mass ratio of 3:1 were dissolved in dichloromethane, and then propargyl alcohol was added dropwise to the above suspension, wherein the mass ratio of 4-methylaminopyridine to propargyl alcohol was 2.5:1, and the mixture was stirred at room temperature for 22-24 h. After the reaction was completed, the mixture was washed with 10% NaHSO4 and then with deionized water. The organic phase was collected, and then N, N'-dicyclohexylcarbodiimide was dissolved in dichloromethane and added dropwise to the above organic phase, wherein the mass ratio of 4-methylaminopyridine to N, N'-dicyclohexylcarbodiimide was 2.5:1. After reacting at 0°C for 1 h, the mixture was allowed to stand to room temperature and stirred for 20-24 h. The reaction mixture was filtered to remove all solids, and evaporated under reduced pressure to obtain compound 1.

[0043] (3) 20 g of white powder and 2 g of compound 2 were dissolved in 20 mL of toluene, the temperature was raised to 70°C and the reaction mixture was maintained for 48 h, then cooled to room temperature, 30 mL of ether was added, and compound 3 was obtained after filtering and drying; the synthesis method of compound 2 was as follows: a mixture of 1,4-butanediol diglycidyl ether, NaN3 and NH4Cl in a mass ratio of 15:24:20 was added to dichloromethane, stirred at 55°C for 20-24 h, cooled to room temperature, washed with 10% NaHSO4, then washed with deionized water, and evaporated under reduced pressure to obtain compound 2.

[0044] (4) 8 g of siloxane, 11 g of compound 3, and 1 g of hexamethylene diisocyanate were added to 10 mL of tetrahydrofuran in sequence, and stirred at 60° C. for 1 h to obtain a prepolymer, and 6.6 g of methacrylic acid, a crosslinking agent, was added and stirred for 1 h; the structural formula of the siloxane is:

[0045]

[0046] In formula (I), R1 is NH2, and R2, R3, R4, R5, R6, and R7 are CH3.

[0047] (5) The solution was poured into a mold and placed in an oven at 100° C. for 12 h to obtain a shape memory polymer.

[0048] Example 3

[0049] A method for preparing a high-stretchability shape memory polymer comprises the following steps:

[0050] (1) Dissolve 24.6 g of butyrolactone and 0.35 g of ethylene glycol in 20 mL of toluene, heat to 100 °C and stir for 2 h;

[0051] (2) After cooling to room temperature, 4.1 g of compound 1 was added, and the mixture was stirred at room temperature for 24 h. The organic layer was collected, dried, and evaporated under reduced pressure to obtain a white powder. The synthesis method of the compound 1 is as follows: succinic anhydride and 4-methylaminopyridine in a mass ratio of 3:1 were dissolved in dichloromethane, and then propargyl alcohol was added dropwise to the above suspension, wherein the mass ratio of 4-methylaminopyridine to propargyl alcohol was 2.5:1, and the mixture was stirred at room temperature for 22-24 h. After the reaction was completed, the mixture was washed with 10% NaHSO4 and then with deionized water. The organic phase was collected, and then N, N'-dicyclohexylcarbodiimide was dissolved in dichloromethane and added dropwise to the above organic phase, wherein the mass ratio of 4-methylaminopyridine to N, N'-dicyclohexylcarbodiimide was 2.5:1. After reacting at 0°C for 1 h, the mixture was allowed to stand to room temperature and stirred for 20-24 h. The reaction mixture was filtered to remove all solids, and evaporated under reduced pressure to obtain compound 1.

[0052] (3) 20 g of white powder and 2 g of compound 2 were dissolved in 20 mL of toluene, the temperature was raised to 70°C and the reaction mixture was maintained for 48 h, then cooled to room temperature, 30 mL of ether was added, and compound 3 was obtained after filtering and drying; the synthesis method of compound 2 was as follows: a mixture of 1,4-butanediol diglycidyl ether, NaN3 and NH4Cl in a mass ratio of 15:24:20 was added to dichloromethane, stirred at 45°C for 20-24 h, cooled to room temperature, washed with 10% NaHSO4, then washed with deionized water, and evaporated under reduced pressure to obtain compound 2.

[0053] (4) 8 g of siloxane, 12 g of compound 3, and 1 g of hexamethylene diisocyanate were added to 10 mL of tetrahydrofuran in sequence, and stirred at 60° C. for 1 h to obtain a prepolymer, and 6.6 g of methacrylic acid, a crosslinking agent, was added and stirred for 1 h; the structural formula of the siloxane is:

[0054]

[0055] In formula (I), R1 is NH2, and R2, R3, R4, R5, R6, and R7 are CH3.

[0056] (5) The solution was poured into a mold and placed in an oven at 100° C. for 12 h to obtain a shape memory polymer.

[0057] A certain mass of sample was cut for differential scanning calorimetry experiment. First, it was heated to 200°C to eliminate the thermal history. After natural cooling, heating and cooling scans were performed. The response temperature of the sample was determined based on the obtained data. The above experiments were all carried out under nitrogen protection.

[0058] The prepared sample strip with a certain size is placed in a drying oven at 90°C for 30 minutes and then folded 180°. The bending angle θ0 of the sample strip is recorded (θ0≈180°). After that, the sample strip is cooled to room temperature while maintaining the external force, and then the external force is removed, and the bending angle θ1 of the sample strip is recorded. Therefore, the shape fixation rate of the prepared sample can be calculated by the following formula.

[0059]

[0060] Prepare the required dumbbell-shaped polymer and composite material standard specimens according to the mechanical testing machine, and then test the static mechanical properties at room temperature. The loading speed of the mechanical testing machine chuck is 1-5mm min -1 Each group of test samples has 3 parallel samples, and finally the average value is taken to calculate the tensile strength, elongation at break and Young's modulus.

[0061] Table 1 Response temperature of the embodiment

[0062] product Response temperature(℃) Example 1 110 Example 2 95 Example 3 88

[0063] Table 2 Shape fixing temperature and shape fixing rate of the embodiment

[0064] product Shape fixing temperature(℃) Shape fixation rate Example 1 130 92.7% Example 2 122 94.9% Example 3 116 97.4%

[0065] Table 3 Mechanical properties of the examples

[0066] product Tensile strength(MPa) Elongation at break (100%) Example 1 20.3 860% Example 2 19.1 1020% Example 3 17.5 1120%

[0067] As shown in the results in the table, it can be seen from the table below that the mechanical properties of shape memory polymers prepared with siloxane and topological ring polymers can be adjusted within a certain range. As the mass of the ring polymer increases, the tensile strength of the shape memory polymer decreases and the elongation at break increases. This is because the chain-free terminal structure of the ring polymer and the molecular ring occupying more space network lead to an increase in the distance between the cross-linking sites and a decrease in the cross-linking network density, thereby improving its ductility.

Claims

1. A method for preparing a high-stretchability shape memory polymer, characterized in that: The method is: Step 1: Dissolve butyrolactone and ethylene glycol in toluene, heat to 100-115°C and stir for 2-3h; Step 2: After cooling to room temperature, add compound 1 having alkynyl groups at both ends, and stir at room temperature for 20-24 hours, collect the organic layer, dry it, and evaporate it under reduced pressure to obtain a white powder; Step 3: dissolving the white powder and compound 2 in toluene, heating the reaction mixture to 60-75°C and maintaining the temperature for 48 hours, then cooling to room temperature, adding an excess of ether relative to the remaining liquid, filtering and drying to obtain compound 3; Step 4: Add siloxane, compound 3, and hexamethylene diisocyanate to tetrahydrofuran in sequence, stir for 1-1.5 hours at 60-75° C. to obtain a prepolymer, add methacrylic acid as a crosslinker in an amount of 1 / 3 of the total mass of siloxane, compound 3, and hexamethylene diisocyanate, and stir for 1-1.5 hours; Step 5: Pour the solution into a mold and place it in an oven at 90-110°C for 10-14 hours to obtain a shape memory polymer.

2. The method for preparing a high-stretchability shape memory polymer according to claim 1, characterized in that: In step 1, the mass fractions of butyrolactone and ethylene glycol are 97wt.% to 98.6wt.% and 1.4wt.% to 3wt.%, respectively.

3. The method for preparing a high-stretchability shape memory polymer according to claim 1, characterized in that: In step 2, the synthesis method of compound 1 is: Succinic anhydride and 4-methylaminopyridine in a mass ratio of 3-4:1 are dissolved in dichloromethane, and then propargyl alcohol is added dropwise to the above suspension, the mass ratio of 4-methylaminopyridine to propargyl alcohol is 2.5-3:1, and stirred at room temperature for 22-24 hours. After the reaction is completed, wash with 10% NaHSO4 and then with deionized water, collect the organic phase, and then dissolve N, N'-dicyclohexylcarbodiimide in dichloromethane, and add dropwise to the above organic phase, the mass ratio of 4-methylaminopyridine to N, N'-dicyclohexylcarbodiimide is 2.5-3:

1. After reacting at 0°C for 1 hour, let stand to room temperature and stir for 20-24 hours. Filter the reaction mixture to remove all solids, and evaporate under reduced pressure to obtain compound 1.

4. The method for preparing a high-stretchability shape memory polymer according to claim 1, characterized in that: In step 2, the mass ratio of compound 1 to butyrolactone is 1:

6.

5. The method for preparing a high-stretchability shape memory polymer according to claim 1, characterized in that: In step 3, the synthesis method of compound 2 is: A mixture of 1,4-butanediol diglycidyl ether, NaN3 and NH4Cl in a mass ratio of 15-18:24:20 was added to dichloromethane, stirred at 40-60°C for 20-24h, cooled to room temperature, washed with 10% NaHSO4, then washed with deionized water, and evaporated under reduced pressure to obtain compound 2.

6. The method for preparing a high-stretchability shape memory polymer according to claim 1, characterized in that: In step 3, the mass ratio of compound 2 to white powder is 1:

10.

7. The method for preparing a high-stretchability shape memory polymer according to claim 1, characterized in that: In step 4, the structural formula of the siloxane is: In formula (I), R1 is NH2, R2, R3, R4, R5, R6, and R7 are independently selected from H, C 1-10 Alkyl, C 6-14 One or more of aromatic groups.

8. The method for preparing a high-stretchability shape memory polymer according to claim 1, characterized in that: In step 4, the mass ratio of the siloxane, compound 3 and hexamethylene diisocyanate is 8:10 to 13:

1.

9. A high stretchability shape memory polymer prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Shape memorizing polyurethane and preparation method thereof

    CN109912773A

  • Preparation method of organosilicone-modified polyurethane shape memory material

    CN110078887A

  • Shape memory recovery method of heat-adaptive shape memory polymer

    CN113004497A

  • AU2003204827B2